TELENURSING AND HEALTH EDUCATION TO IMPROVE FLUID RESTRICTION COMPLIANCE IN CHRONIC KIDNEY DISEASE PATIENTS WITH HYPERVOLEMIA UNDERGOING HEMODIALYSIS: CASE STUDY - Ermawati, Eli; Hidayati, Wahyu (Ikatan Lembaga Mahasiswa Ilmu Keperawatan Indonesia, 2024)
Background: Patients with chronic kidney disease (CKD) who are undergoing hemodialysis therapy are important to limit fluids to prevent fluid buildup that can trigger complications. Increased fluid volume, both intravascular and interstitial, can cause hypervolemia. Telenursing is the use of technological resources and communication systems to promote nursing development. This study is to determine the application of telenursing and health education to improve adherence to fluid restriction in CKD patients undergoing hemodialysis. Methods: This research is a case study on three patients with hypervolemia. The interventions provided were health education twice and telenursing via short messages for six days. The instrument used in this study used an adaptation of the ESRD-AQ questionnaire to measure adherence to fluid restriction and was supported by clinical data on blood pressure, IDWG, UF goal, and degree of edema. Results: The results of this study are that the level of adherence before the intervention was given was 100% non-adherent. After being given the intervention, 66.7% (Mrs. N. and Mrs. S.) were compliant, and 33.3% of Mr. T. did not comply with fluid restrictions. Conclusion: Health education and telenursing in the form of short message reminders can improve compliance with fluid restriction in CKD patients with hypervolemia. Recommendations from research can determine effective health education methods and media as well as telenursing media for patients and families.